Enantioselective synthesis of dihydroquinazolinone derivatives catalyzed by a chiral organocatalyst. (11th July 2017) - Ayyanar, Siva; Vijaya, Ponmuthu Kottala; Mariyappan, Madhappan; Ashokkumar, Veeramanoharan; Sadhasivam, Velu; Balakrishnan, Sankar; Chinnadurai, Chithiraikumar; Murugesan, Sepperumal
Abstract : The asymmetric condensation/amine addition cascade reaction catalysed by a effective chiral organocatalyst for the formation of 2, 3-dihydroquinazolinones with high yields (up to 99%) and ee's (up to 97%). Abstract : The asymmetric condensation/amine addition cascade sequence of 2-aminobenzamide and aldehydes, catalyzed by a novel chiral organocatalyst, was realized. The organocatalyst was found to be very effective and highly enantioselective for such cascade reactions at room temperature, affording 2, 3-dihydroquinazolinones in excellent yields (up to 99%) with enantiomeric excesses of up to 97%. The best level of stereocontrol was obtained for aromatic/aliphatic aldehydes with ortho, para or meta substituents.